2013
DOI: 10.1128/jb.00563-13
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Catalases in Members of the Chlamydiales Order

Abstract: Catalase is an important virulence factor for survival in macrophages and other phagocytic cells. In Chlamydiaceae, no catalase had been described so far. With the sequencing and annotation of the full genomes of Chlamydia-related bacteria, the presence of different catalase-encoding genes has been documented. However, their distribution in the Chlamydiales order and the functionality of these catalases remain unknown. Phylogeny of chlamydial catalases was inferred using MrBayes, maximum likelihood, and maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…A recent work by Rusconi and Greub (), demonstrated that, contrarily to Chlamydiaceae , several Chlamydia ‐related bacteria possess a functional catalase, an enzyme likely important for survival in phagocytic cells such as macrophages. The total absence of this enzyme in Chlamydiaceae might be one reason why the macrophage and amoebal environments are hostile to these bacteria (Wirz et al ., ; Beagley et al ., ).…”
Section: Challenging the Concept Of Arm As Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent work by Rusconi and Greub (), demonstrated that, contrarily to Chlamydiaceae , several Chlamydia ‐related bacteria possess a functional catalase, an enzyme likely important for survival in phagocytic cells such as macrophages. The total absence of this enzyme in Chlamydiaceae might be one reason why the macrophage and amoebal environments are hostile to these bacteria (Wirz et al ., ; Beagley et al ., ).…”
Section: Challenging the Concept Of Arm As Pathogensmentioning
confidence: 99%
“…It can detect five DNA copies of any member of the Chlamydiales order, exhibits a high specificity for bacteria of this order and does not amplify DNA of any other bacterial clade (Lienard et al ., 2011b). This new PCR may fill the gap generally left when using conventional eubacterial PCR. Because of particular features of their extracellular membrane (Rusconi and Greub, ; Rusconi et al ., ), chlamydial elementary bodies are highly resistant to classical bacterial lysis protocols thus hampering DNA extraction (Croxatto et al ., ). An alternate extraction protocol has thus been set up (Croxatto et al ., ) that includes a 2 h proteinase K digestion step ensuring complete bacterial membrane lysis and consequently efficient DNA extraction. Chlamydiales bacteria are obligate intracellular organisms strictly dependent of an eukaryotic host for multiplication.…”
Section: Challenging the Concept Of Arm As Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterium was also shown to grow in two fish cell lines but could not induce cell lysis (Kebbi-Beghdadi et al, 2011 ). Survival and growth in macrophages and other professional phagocytes is made possible by the presence of a class 3 catalase that degrade reactive oxygen species (Rusconi and Greub, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…¶ ¶Putative Pmp encoded in the genome, but not isolated at the membrane. § § (Collingro et al, 2011;Rusconi & Greub, 2013). jjjj (Bertelli et al, 2010;Carlson et al, 2006;Collingro et al, 2011;Horn et al, 2004;Knab et al, 2011;Omsland et al, 2014).…”
Section: Cell Wall and Surface Proteinsmentioning
confidence: 99%